2010
DOI: 10.1590/s1414-81452010000400024
|View full text |Cite
|
Sign up to set email alerts
|

Percepção de idosos com doença pulmonar obstrutiva crônica sobre a qualidade de vida

Abstract: Objetivou analisar a percepção de idosos com doença pulmonar obstrutiva crônica sobre a qualidade de vida. Os dados foram coletados com 24 idosos aplicando o instrumento World Health Organization Quality of Life-100, orientado pelo conceito de qualidade de vida da Organização Mundial da Saúde, composto pelos domínios Físico, Psicológico, Nível de independência, Relações sociais e Religiosidade. A análise descritiva demonstrou média e desvio-padrão dos escores para tais domínios, respectivamente: 11,15±2,58, 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
2
0
1
Order By: Relevance
“…(13) Likewise, two other studies involving similar populations showed that a low level of education resulted in worse QoL. (19,20) Most of the patients in the present study were overweight or obese. Having a higher BMI correlated negatively with the mental health domain.…”
Section: Discussionsupporting
confidence: 62%
“…(13) Likewise, two other studies involving similar populations showed that a low level of education resulted in worse QoL. (19,20) Most of the patients in the present study were overweight or obese. Having a higher BMI correlated negatively with the mental health domain.…”
Section: Discussionsupporting
confidence: 62%
“…Autonomy is a determining factor in the life quality, because it enables to make daily decisions. 16 Chronic disease may act as a force that drives relatives to focus intensively on patient´s care, relegate biopsychosocial aspects of the family life and elect the primary caregiver of that individual. This fact may, in some cases, generate the exchange of roles.…”
Section: ] (P6f)mentioning
confidence: 99%
“…Individuals' education level is also a relevant data for discussion since it is directly related to their self-care capacity and quality of life, with direct repercussions on the evolution of chronic diseases [15,34,35]. Thus, as in many other studies [15,18], the education level most commonly observed was incomplete primary education (33.9%), suggesting that both self-care and quality of life could be harmed among these individuals.…”
Section: Discussionmentioning
confidence: 91%